Do bordel às aparelhagens: a música brega paraense e a cultura popular massiva - Silva, Expedito Leandro (2009)
The analysis of this study addresses how and to what extent a mass culture and popular excluded from the mainstream media, interact to achieve and maintain their space as well as the popular music of Pará state, specifically the style cheesiness, and playful as a manifestation interactive sociability in the popular culture of Para, in addition to its important relationship and proximity to the Caribbean musicality. Since the bolero, merengue and style corny, interact with the panorama of the Brazilian cultural industry and local music, specifically the stamp. The style is tacky understood as a popular manifestation which brings its historical legacies, today called corny calypso. Analyzes the festive sociability, culture and leisure itself in the Amazon region as it integrates inland populations and large cities. Finally, there is the productive chain of musical manifestation, leisure and entertainment around the tecnobrega, in Bethlehem, took a prominent position, has emerged as a means of source of income and employment, through live presentations, the festivals, recordings from CD and DVD among others. Movement tecnobrega introduced a model of the music market and culture that is not restricted to economic issues, but also to social factors of local culture. It appears that the actors in this market range from artists (composer, singers, dancers, members of bands), DJs, sound systems and studios (producers and music players), vendors (vendor), party planners and homeowners to festivals, presenters and program directors of radio and TV, among others